Age Differences in Prospective Memory: A Further Evaluation of the Executive Framework. Issue 5 (20th October 2019) - Zhao, Xin; Fu, Junjun; Ma, Xiaofeng; Maes, Joseph H.R.
ABSTRACT: According to the executive framework of prospective memory (PM), age-related differences in PM performance are mediated by age-related differences in executive functioning (EF). The present study further explored this framework by examining which specific components of EF are associated with PM differences between and within three age groups. A group of children (7–9 years; N = 108), adolescents (12–14 years; N = 112), and adults (17–23 years; N = 106) performed focal- and non-focal event-based PM (EBPM) tasks, a time-based PM (TBPM) task, and tasks measuring EF components. Differences between age groups in focal EBPM, non-focal EBPM, and TBPM performance were mediated by, respectively, differences in interference control and response inhibition, performance on the ongoing task, and differences in working memory and response inhibition. However, within-age group analyses only revealed WM updating as significant predictor of TBPM performance in the adolescent group. These results support and further qualify the executive framework of PM. The differences in outcome dependent on the examined age range might be important for explaining mixed results of previous studies regarding the precise EF components underlying age-related PM task performance differences.